Perancangan Karakter Sura dan Baya sebagai Representasi Ikon Surabaya pada Ondomohen 1896 - Nabila Kusuma Wardani; Aninditya Daniar; Diana Aqidatun Nisa (IAI Nasional Laa Roiba Bogor, 2026)
Character design plays a significant role in strengthening visual identity, particularly for local brands rooted in cultural values. This study aims to design reinterpretative characters of Surabaya’s Sura and Baya to reinforce the identity of Ondomohen 1896 and connect it with Generation Z. The research employs a mixed methods approach using the Double Diamond framework, with data collected through interviews, questionnaires, and literature review. Findings show that 63.9% of respondents value unique local-themed design, while expressive and high-contrast visuals are preferred by young audiences. Based on these insights, contemporary characters were developed to combine local identity with a modern visual approach. The results indicate that character design can effectively strengthen local brand identity while remaining relevant to current visual trends.